Formation of the high-intensity microsecond flow of electrons in the channel of high pressure arc discharge - Volkolupov, Yu.Ya.; Kolyada, Yu.E.; Krasnogolovets, M.A.; Onishchenko, I.N.; Fedun, V.I. (Вопросы атомной науки и техники, 2000)
The possibility of microsecond duration powerful electron flows formation in the channel of high current arc discharge at atmosphere pressure has been experimentally demonstrated. The flow of electrons is formed at applying the high voltage pulse to the plasma source after plasma ejection and the pressure decreasing. Because the acceleration by the electric field prevails over the friction force due to collisions the conditions for arising of running electrons are fulfilled.